Somatic characteristics and body composition in Czech sub-elite female handball players - Ivana Kinkorová; Eva Brožová; Martin Komarc (Karolinum Press, 2020)
The somatic parameters and body composition are important indicators of physical fitness and general health not only non-athletes, but of athletes. The aim of this study was to determine the somatic characteristics and body composition in 15 Czech sub-elite female handball players (age 21.5 ± 1.8 years, body height 170.5 ± 6.6 cm, body weight 64.7 ± 10.2 kg, BMI 22.2 ± 2.9 kg m−2). Body composition was measured by a multifrequency bioimpedance method Tanita MC-980 (Tanita Europe BV). The monitored parameters were the following: fat mass (FM), fat free mass (FFM), muscle mass (MM), bone mass (BM), total body water (TBW), intracellular water (ICW), extracellular water (ECW) and segmental analysis of muscle distribution. In our female group, we recorded the mean value of FM = 21.5 ± 5.4% (14.3 ± 5.7 kg), FFM = 50.4 ± 5.9 kg, muscle mass = 47.9 ± 5.6 kg, bone mass = 2.6 ± 0.3 kg, TBW = 56.2 ± 3.2% (36.2 ± 4.8 kg), ICW = 22.6 ± 3.5 kg, ECW = 13.6 ± 1.3 kg. Monitoring of muscle distribution in the extremities showed a significant difference in upper extremities (p < 0.05, ES < 0.2) and in lower extremities (p < 0.05, ES < 0.2). Our results confirm on previous data about the presence of anthropometric differences and body composition differences between individual players in handball team.